Market-Based Algorithms for Allocating Complex Tasks - Zheng, Xiaoming; Koenig, Sven (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
In this abstract we extended previous research to the allocation of complex tasks, where complex tasks need to be performed by several agents simultaneously. We proposed reaction functions to succinctly characterize the agent costs for executing complex tasks at given times and illustrated an important property of the execution times of complex tasks that minimize the team cost, which facilitates winner determination by the auctioneer.